Contaminação radioativa: aspectos fundamentais associados à poluição nuclear - Pasetti, Carolina Manabe [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Since its discovery, radioactivity has brought numerous benefits to human societies. It has many applications in medicine, serving as a tool for non-invasive methods for diagnosis and therapies against diseases such as cancer. It also applies to technologies for energy in nuclear power plants with relatively low impacts on terms of perfect security. All applications, however, have risks, requiring maximum caution to drive processes and operations involving radioactive elements because, once released into the environment, they have extremely harmful effects on organisms affected. This paper presents fundamental concepts and principles of nuclear physics in order to understand the effects of radioactive elements released into the environment, culminating on the issue of radioactive contamination. Literature review allowed us to understand the radioactive contamination problem on living beings. Three major nuclear accidents have happened in the last thirty years, two of them in consecutive years. The nuclear accident at Chernobyl, Ukraine, in 1986, polluted large areas, condemning hundreds of thousands of people to live with consequences of the accident and effects of radiation, killing thousands of people throughout the years. In 1987, a major radiological accident occurred in Goiania (GO) when a source of radioactive cesium was violated, leading to the death of those who had direct or indirect contact with cesium. The most recent accident, in March, 2011, was located at the nuclear power plant in Fukushima Prefecture, Japan, after an earthquake and tsunami hit the region. There is no extensive and accurate knowledge about the consequences of the contamination entailed in that accident, although it is possible to verify signals on a global scale. An analysis of reports of contamination of large areas generated by nuclear plants with release of hazardous wastes suggests it is necessary to rethink the energy matrix of the various countries...

A radioatividade, desde sua descoberta, tem trazido inúmeros benefícios à sociedade. Possui diversas aplicações na medicina, servindo como ferramenta em métodos não invasivos para diagnósticos e em terapias contra enfermidades, tais como câncer. Aplica-se também a tecnologias para obtenção de energia em usinas nucleares, com impactos ambientais relativamente baixos em condições de perfeita segurança. Todas as aplicações, porém, possuem riscos, exigindo-se precaução para conduzir processos e operações envolvendo elementos radioativos, pois, uma vez liberados no meio ambiente, possuem consequências extremamente nocivas sobre os organismos afetados. A revisão bibliográfica possibilitou a compreensão da problemática da contaminação radioativa sobre os organismos vivos. Três grandes acidentes nucleares aconteceram nos últimos trinta anos, dois deles em anos consecutivos. O acidente nuclear de Chernobyl, na Ucrânia, em 1986, contaminou extensas áreas, condenando centenas de milhares de pessoas a conviverem com as consequências do acidente e os efeitos da radiação, vitimando milhares de pessoas ao longo dos anos. Em 1987, ocorreu em Goiânia (GO) um dos maiores acidentes radiológicos da história brasileira, quando se violou uma fonte de césio radioativo, liberando radionuclídeos e contaminando diversas áreas da cidade, levando a óbito muitos daqueles que tiveram contato direto ou indireto com o césio. O acidente mais recente, em março de 2011, ocorreu na usina nuclear localizada na província de Fukushima, no Japão, após um terremoto seguido de tsunami, que atingiu a região. Ainda não há um extenso e preciso conhecimento sobre as consequências da contaminação acarretada pelo acidente, mas já é possível verificar sinais em escala global. O presente trabalho apresenta conceitos e princípios fundamentais de Física Nuclear, visando ao entendimento dos efeitos dos elementos radioativos liberados no meio...
Keywords: Radiação; Poluição radioativa; Radioatividade; Usinas nucleares - Acidentes; Contaminação